Maternal effect on seed survival and emergence in Cytisus scoparius: an experimental approach. Issue 6 (28th August 2013) - Magda, Danièle; Gleizes, Benoit; Jarry, Marc
Abstract: The role of the individual origin of seeds in the variability of demographic parameters within a seed‐bank has been little studied despite the recognition of its important contribution to species adaptation strategies to environmental constraints. This study analyzed the seed‐bank dynamics of Cytisus scoparius, a small woody species with a high aptitude for colonization and dominance. Our experimental setup made it possible to monitor seed emergence dynamics in situ for maternal individuals within the study population. In addition to the characteristic traits of the species (maximum seed life span between 4 and 5 years in 75 % of the cases), there was a high variability of the emergence dynamics between individuals, distinguished both by their total emergence rate and profile. The total emergence rate of seeds was correlated with their quality (seed weight and number of seeds per pod), but was unrelated to either maternal age or fecundity. Different emergence profiles can be recognized between two distinct patterns: on one hand, a strategy that concentrates on emergence in the second year and, on the other, a regular decrease of the germinant number over time. The coexistence of different seed‐bank strategies between individuals results in the ability for the population to face to disturbances and environmental variability.